2013
DOI: 10.1093/hmg/dds556
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific induced-pluripotent stem cells-derived cardiomyocytes recapitulate the pathogenic phenotypes of dilated cardiomyopathy due to a novel DES mutation identified by whole exome sequencing

Abstract: In this paper, we report a novel heterozygous mutation of A285V codon conversion on exon 4 of the desmin (DES), using whole exome sequencing (WES) in an isolated proband with documented dilated cardiomyopathy (DCM). This mutation is predicted to cause three-dimensional structure changes of DES. Immunohistological and electron microscopy studies demonstrated diffuse abnormal DES aggregations in DCM-induced-pluripotent stem cell (iPSC)-derived cardiomyocytes, and control-iPSC-derived cardiomyocytes transduced wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 27 publications
1
55
0
Order By: Relevance
“…In addition, contraction arrest was observed in the mutant cardiomyocytes upon isoproterenol stimulation. These observations not only provided an explanation to the pathogenic mechanism underlying the DES A285V mutation, but also validated the causal ion relationship between the DES mutation and the DCM phenotype observed in that patient [49]. …”
Section: Applications Of Ipscs-derived Cardiomyocytes In Modeling supporting
confidence: 65%
See 1 more Smart Citation
“…In addition, contraction arrest was observed in the mutant cardiomyocytes upon isoproterenol stimulation. These observations not only provided an explanation to the pathogenic mechanism underlying the DES A285V mutation, but also validated the causal ion relationship between the DES mutation and the DCM phenotype observed in that patient [49]. …”
Section: Applications Of Ipscs-derived Cardiomyocytes In Modeling supporting
confidence: 65%
“…Lately, by utilizing the whole-exome sequencing approach, our laboratory has identified a novel DES mutation in a patient with left ventricular dilation and impaired left ventricular ejection function [49]. In this DES mutation, we recognized a change of the alanine (A) residue to valine (V) at the 285th amino acid position.…”
Section: Applications Of Ipscs-derived Cardiomyocytes In Modeling mentioning
confidence: 99%
“…80, 81 Most recently, DCMs due to mutations that truncate the massive sarcomere protein titin (TTNtvs) were modeled using hiPSC-derived 3-dimensional cardiac microtissues (CMTs), which had the advantage of yielding more mature cardiac phenotypes than a monolayer of hiPSC-CMs. 105 In this study, patient-derived CMTs with TTNtvs developed sarcomere insufficiency, impaired contractile response to mechanical or beta-adrenergic stress, as well as attenuated growth factor signaling activation.…”
Section: Disease Modeling Using Patient-specific Hipsc Derivativesmentioning
confidence: 99%
“…These results clearly showed a genetic component to the development of diabetic cardiomyopathy because the diseased hiPSC-CMs behaved differently at baseline from those of normal hiPSC-CMs. Conceivably, many other cardiomyopathies thought to be acquired could also have a genetic component and are worth studying using hiPSC-CMs (e.g., chemotherapy-induced cardiomyopathy, 111 alcohol cardiomyopathy, viral cardiomyopathy 81 ).…”
Section: Disease Modeling Using Patient-specific Hipsc Derivativesmentioning
confidence: 99%
“…It should be noted that the R173W mutation identified in these DCM patients had not been previously reported, and was discovered in this family cohort following exome sequencing of the skin fibroblasts used to generate hiPSCs. In separate studies, hiPSC-CMs carrying DCM-associated mutations in the spliceosome RNA-binding motif protein 20 (RBM20), lamin A/C (LMNA/C), or desmin (DES) genes (243,275,304) also demonstrated abnormalities that closely recapitulate the morphological and functional phenotypes of the affected human heart, as outlined in hiPSC models of HCM associated with thick myofilament myosin heavy chain 7 (MYH7) (89,148) or myosin binding protein C3 (MYBPC3) (262) mutations showed that in vitroderived hiPSC-CMs are significantly enlarged, as seen in the diseased human myocardium. hiPSC-CMs also demonstrated increased myofibril content, contractile arrhythmias (DADs), Ca 2ϩ cycling perturbations, and intracellular Ca 2ϩ elevation, which were worsened by adrenergic stimulation (e.g., with isoproterenol) or environmental exposure to the potent vasoconstrictor endothelin-1 (ET-1) (310).…”
Section: B Cardiomyopathiesmentioning
confidence: 99%